Feasibility and acceptability of an oral pathology asynchronous tele-mentoring intervention: A protocol - Mary E. Northridge; Tina Littlejohn; Nathalie Mohadjeri-Franck; Steven Gargano; Andrea B. Troxel; Yinxiang Wu; Robert B. Bowe; Paul A. Testa (SAGE Publishing, 2020)
Introduction: Oral cancer remains prevalent, despite being largely preventable. The widespread use of technology at chairside, combined with advances in electronic health record (EHR) capabilities, present opportunities to improve oral cancer screening by dentists, especially for disadvantaged patients with severe health needs. Design and methods: Using a mixed-methods approach, we will evaluate the feasibility and acceptability of integrating a tele-mentoring component into the identification of oral lesions using the following 3 methods: 1) administering provider surveys that consist of a checklist of 10 key components of the intervention based on process, and asking the dental provider subjects if each one was covered; 2) conducting semi-structured interviews informed by the Consolidated Framework for Implementation Research and the Implementation Outcomes Framework with dental resident subjects to assess specific barriers to sustaining the intervention and strategies for addressing these barriers to facilitate integration of the intervention into the routine workflow of the dental clinics; and 3) administering brief exit interviews with patient subjects regarding the acceptability of the intervention to assess satisfaction with the use of intra-oral cameras at chairside to screen for and refer patients with oral lesions and identification of these oral lesions via EHR and secure e-mail tele-mentoring with an oral pathology expert. Expected impact of the study for public health: If successful, then later clinical trials will maximize the external validity of the intervention and facilitate the widespread implementation and dissemination of the model for the teaching of dentists and residents, with the ultimate goal of improving patient care.